Battlestar galactica - Dykstra, John; Stevens, Leslie; Larson, Glen A.; Colla, Richard A. (Universal City, CA : Universal, 2003)
In the deepest reaches of space, the fight to save all human life from extinction has begun. Hoping for lasting peace following centuries of intense warfare, the Twelve Colonies gather to sign a treaty with their dreaded enemies, the Cylons. But after an act of treachery, the Cylons launch a devasting surprise attack, destroying the Colonies home planet. A lone flagship, the Galactica, remains to aid the surviving colonists on their epic journey to their new home - far-off Earth
Title from title screen
Cinematographer, Ben Colman ; editors, Robert L. Kimble, Leon Ortiz-Gil, Larry Strong ; original music, Stu Phillips ; production designer, Ralph McQuarrie ; special effects, John Dykstra
Cast: Richard Hatch, Dirk Benedict, Lorne Greene, Herb Jefferson, Jr. Maren Jensen, Tony Swartz, Noah Hathaway, Terry Carter, Lew Ayres, Wilfrid Hyde-White, John Colicos, Laurette Spang, John Fink, Jane Seymour, Ray Milland
DVD Format
Keywords: Space colonies -- Drama; Treaties -- Drama; War -- Drama